2006
DOI: 10.1523/jneurosci.0672-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral-Mediated Modulation ofSim1Expression in the Paraventricular Nucleus Affects Food Intake

Abstract: Haploinsufficency of Sim1, which codes for a basic helix-loop-helix-PAS (PER-ARNT-SIM) transcription factor, causes hyperphagia in mice and humans, without decrease in energy expenditure. Sim1 is expressed in several areas of the brain, including the developing and postnatal paraventricular nucleus (PVN), a region of the hypothalamus that controls food intake. We have previously found that the number of PVN cells is decreased in Sim1 ϩ/Ϫ mice, suggesting that their hyperphagia is caused by a developmental mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 17 publications
3
40
0
Order By: Relevance
“…Mouse models have shown Sim1 to play both a developmental and a postnatal physiological role in this nucleus (2-4, 6, 34), with evidence divided as to whether 1 functional copy of Sim1 is sufficient for its developmental function (4,35). Consistent with postnatal deletion of Sim1 causing hyperphagia (6), stereotaxic injection of an adenovirus expressing shRNA directed against Sim1 into the PVN has shown that reduction of Sim1 expression in a subset of neurons is sufficient to affect food intake (36) Ad libitum energy intake was increased in patients with SIM1 variants with no evidence of a defect in basal energy expenditure. SIM1 variant carriers had lower blood pressure measurements, showed an attenuated increase in heart rate on waking, and had increased respiratory quotients when compared with obese controls.…”
Section: Figurementioning
confidence: 99%
“…Mouse models have shown Sim1 to play both a developmental and a postnatal physiological role in this nucleus (2-4, 6, 34), with evidence divided as to whether 1 functional copy of Sim1 is sufficient for its developmental function (4,35). Consistent with postnatal deletion of Sim1 causing hyperphagia (6), stereotaxic injection of an adenovirus expressing shRNA directed against Sim1 into the PVN has shown that reduction of Sim1 expression in a subset of neurons is sufficient to affect food intake (36) Ad libitum energy intake was increased in patients with SIM1 variants with no evidence of a defect in basal energy expenditure. SIM1 variant carriers had lower blood pressure measurements, showed an attenuated increase in heart rate on waking, and had increased respiratory quotients when compared with obese controls.…”
Section: Figurementioning
confidence: 99%
“…Sim1-haploinsufficient mice display hypodevelopment of the paraventricular nucleus of the hypothalamus and are hyperphagic, obese, and highly sensitive to diet-induced obesity, whereas Sim1 overexpression in mice leads to a decrease in food intake (2)(3)(4). In humans, several deletions in the chromosome 6q16, the region that includes SIM1, have been identified in obese patients presenting with a Prader-Willi-like (PWL-like) syndrome (5), which is characterized in early infancy by global developmental delay, hypotonia, and feeding difficulties and later in life by hyperphagia, obesity, and facial dysmorphisms (6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, transgenic overexpression of Sim1 conferred resistance to obesity induced either by HF diet or by the A y mutation that abrogates CNS Mc3r and Mc4r signaling (10). Moreover, Yang et al (11) showed that viral-mediated increase or decrease in Sim1 expression in the hypothalamus of adult mice acutely reduced or increased food intake, respectively. Finally, we used a neural-specific Cre transgene whose expression begins postnatally to conditionally inactivate Sim1 after birth, and showed that these mice develop hyperphagic obesity without loss of PVN neurons or gross alteration of hindbrain projections that are thought to mediate satiety (12).…”
mentioning
confidence: 99%